2014
DOI: 10.1016/j.jjcc.2013.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Ten years of experience with closure of persistent foramen ovale: Patient characteristics and outcomes

Abstract: This "all-comers" population documents the safety of percutaneous PFO closure. The cardiovascular event rate is slightly lower (0.26 per 100 patient years) compared to the recently published randomized trials and maintained persistently low rate for more than 8 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…It must be emphasized that closure of PFO is not risk-free [33], because surgical procedures to manage complications of transcatheter interventions may be needed in up to 8% of cases [34]. Although serious complications such as thrombus formation on the implant device, thromboembolism related to the implant device, cardiac perforation, infective endocarditis, and cardiac arrhythmias have been reported [33], the recent ''all-comers'' population in a study by Lehmann et al [35] documented the longterm safety of percutaneous PFO closure (cardiovascular event rate, 0.26 per 100 patient years). Sathasivam et al [33] concluded in their recent review that currently PFO closure cannot be recommended as a routine treatment for migraine for 3 main reasons: (1) the pathophysiological relevance of this procedure in migraine treatment is debatable; (2) the efficacy of this procedure in migraine treatment is inconclusively proven; and (3) the complications of this procedure may be serious and significant in comparison to the non-life threatening nature of migraine.…”
Section: Discussionmentioning
confidence: 99%
“…It must be emphasized that closure of PFO is not risk-free [33], because surgical procedures to manage complications of transcatheter interventions may be needed in up to 8% of cases [34]. Although serious complications such as thrombus formation on the implant device, thromboembolism related to the implant device, cardiac perforation, infective endocarditis, and cardiac arrhythmias have been reported [33], the recent ''all-comers'' population in a study by Lehmann et al [35] documented the longterm safety of percutaneous PFO closure (cardiovascular event rate, 0.26 per 100 patient years). Sathasivam et al [33] concluded in their recent review that currently PFO closure cannot be recommended as a routine treatment for migraine for 3 main reasons: (1) the pathophysiological relevance of this procedure in migraine treatment is debatable; (2) the efficacy of this procedure in migraine treatment is inconclusively proven; and (3) the complications of this procedure may be serious and significant in comparison to the non-life threatening nature of migraine.…”
Section: Discussionmentioning
confidence: 99%
“…ASD je však najčastejšou vrodenou vývojovou chybou srdca diagnostikovanou v dospelosti s podielom viac ako 25 %. 1,2 Ak priemer defektu nepresahuje 5 mm a súčasne nie sú žiadne známky pravostranného objemového kardiálneho preťaženia, nie je terapia indikovaná. 3 Terapia ASD je indikovaná pri dokumentovanej náhlej cievnej mozgovej príhode alebo iných komplikáciách a/alebo ak priemer defektu je viac ako 5 mm a/alebo ak pomer pulmonálno-systémového tlaku (Qp : Qs) je minimálne 1,5 : 1.…”
Section: úVodunclassified
“…The same analysis also examined 52 single-arm studies and, when combined with the comparative studies, found an incidence rate of 0.36 events (95 % CI, 0.24-0.56) per 100 person-years in the closure group versus 2.53 events (95 % CI, 1.91-3.35) per 100 person-years with medical therapy [19]. Lehmann et al reported on ten years of experience, describing 146 consecutive closures at a single center, with a mean follow-up of 7.8±3.1 years, during which 97.9 % of patients experienced no events [35].…”
Section: Evidence For Percutaneous Device Closurementioning
confidence: 99%